Islamic Schools Responses Toward Challenges in the Field of Education to Cope With the 4.0 Industrial Revolution; Study at Yogyakarta State Islamic Senior High School and Semarang Regency State Islamic Senior High School - Nursikin, Mukh; Triyoko, Hanung (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2023)
The progress and development of a nation depends on its education. There is no developed and developing nation without going through a strong and relevant education ladder supported by technological advances. Islamic educational institutions must be able to work together to instill religious moral character, optimal performance, 21st century competences and basic literacy competencies so that students are able to face the era of the Industrial Revolution 4.0. The focus of this research is to emphasize the constructive methodological aspects of the responses of Madrasah Aliyah Negeri Yogyakarta and Madrasah Aliyah Negeri Kab Semarang to the challenges of the industrial revolution 4.0 with a progressivism approach perspective with its liberation paradigm. The purpose of this study is to find out the response and strategy of Islamic educational institutions (Madrasas) in facing the challenges of the 4.0 industrial revolution with an Islamic education philosophy approach that has a liberation paradigm. The theory underlying this study is the theory of modern educational philosophy, namely; (1) Progressivism, (2) Constructivism, and (3) Humanistic schools of thought. Even though these three perspectives of education have different cultural paradigms, there are certain aspects that can contribute cognitively to the development of Islamic education curriculum in schools. This study uses a qualitative-naturalistic approach with data collection from both literature research and field research. Literature research comes from research on dissertations, journals, print media, theses, graduating papers, the internet, and other documents. The field data were collected through (1) observation, (2) in-depth interviews, and (3) documentation. The collected data is then followed by the description, reduction, selection, discussion, analysis and conclusion stages. The results of this study indicate that first, the response of Madrasas to the challenges of the world of education towards the 4.0 industrial revolution is a variety of learning that focuses on the education of characters of the students, then accompanied by the use of technology as an effort to adapt to the advancement of the era, a creation of effective schools, the implementation of the student management, activities which is directed to organize all activities related to students. Second, the Madrasah particular strategy towards the challenges of the world of education in the industrial revolution 4.0. which are the development of Information Technology-Based Madrasah Education and One Stop Integrated Services. This service is to provide fast and coordinated services under the same roof for students, parents, guardians, staff and stakeholders. Students are required to master technology and information at least by mastering 3 software of the Microsoft such as Microsoft Word, Excel, and Power Point. Third, identification of the supporting and inhibiting factors for Madrasas against the challenges of the world of education towards the 4.0 industrial revolution. Supporting factors; The head of Madrasas provides support and assistances, the head of Madrasas and the academic community are united in team work in all fields, the availability of the programmed academic workshops, of IT facilities and infrastructure and adequate practices, the graduation standards already is also established, Networking with the world of works outside schools is also maintained. While the inhibiting factors are that the curriculum is still understood and treated rigidly so that it curbs the creativity of students, the motivation of students to develop themselves is still low, the student's personality is still unstable and tend to love imitating friends behaviors and disobeying norms, the spirit of student competence is still low and the students are mostly not empowered. There is a high level of struggle, the students have not been able to make a priority scale, the facilities and infrastructure for developing self-actualization are still lacking, the tradition of excellence for each academic community in interacting with every level of society and also in information and technology is still low.